Inversions of chromosomes 2 and 6 in mantle cell lymphoma. Cytogenetic, FISH, and molecular studies - Pedrazzini, Estela Marta (2006)
Inversions are infrequent events in hematological malignancies. We here report the cytogenetic, fluorescence in situ hybridization (FISH), and molecular studies of 2 patients diagnosed with mantle cell lymphoma (MCL) that showed inversions of chromosomes 2 and 6 as part of complex karyotypes. Both patients showed a cytogenetically identical inv(6)(p23q11) detected as a secondary aberration. In addition, both patients had a derivative chromosome 2 which originated by partial deletion of the short arm and a pericentric inversion with different breakpoints on the long arm: der(2)del(2)(p21)inv(2)(p21q11) and der(2)del(2)(p21)inv(2)(p21q13), respectively. The presence of t(11;14)(q13;q32) was confirmed by interphase FISH and by molecular study. Residual normal cells were found in both cases. The patients showed a different clinical evolution with a poor outcome for one case and a favorable course of the disease for the other one. The review of the literature in MCL showed a total of 9 inversions affecting different chromosomes. Considering that inversions are very infrequent events in MCL, our findings could be important for detecting genes potentially involved in development and/or progression of this aggressive non-Hodgkin lymphoma subtype. © 2006 Elsevier Inc. All rights reserved.